Moralism and Anti-Moralism: Aspects of Bonhoeffer’s Christian Ethic - Coady, C. A. J. (Sophia, 2012)
Dietrich Bonhoeffer's thinking about ethics and Christianity is a fascinating attempt to combine different, and often conflicting, strands in the Christian intellectual tradition. In this article, I outline his thinking, analyse the advantages and disadvantages in his approach, and relate it to developments in contemporary philosophy. His critique of an excessive stress upon principles and abstraction in opposition to a concern for concrete circumstances is, I argue, best seen as a necessary critique of what I call moralism rather than morality. It is also related to recent philosophical theories of particularism and the debates about ‘emergency ethics’ in current philosophy. On the negative side, Bonhoeffer has a tendency to treat non-Christian ethics as necessarily relativist and at times is excessively influenced by the elements in Christian theological tradition that are hostile to the natural and to non-Christian philosophy. In addition, his invocation of ‘the Divine mandates’ seems to have undesirable implications for some genuine values in liberal democratic theory and practice.